Effects of Different Aged Logged-Over Forests on the Great Argus (Argusianus Argus) (Linnaeus) at Sungai Lalang Forest Reserve, Malaysia - Phirasack, Sengrath (2001)
The Great Argus (Argusianus argus argus) is a moderately large size bird compared to other pheasant species. It belongs to the family Phasianidae and subfamily Argusianinae. This subspecies of Great Argus is found in most lowland and hill Dipterocarp forests up to 818 m above sea level, but is absent from heavily disturbed and fragmented forest sites. The species is considered a threatened species even though it is widely distributed throughout Peninsular Malaysia. An in-depth study of the Great Argus was conducted in three different areas i.e. Virgin Jungle Reserve (VJR), ten-year-old logged forest (C33) and five-year-old logged forest (CI8) at Sungai Lalang Forest Reserve, Selangor, Peninsular Malaysia. The purpose of the study was to examine the distribution of the Great Argus at different elevations, to determine the population density in Virgin Jungle Reserve a well as logged forest and to compare its density in relation to the microclimate, microhabitat and arthropod abundance. Data was collected from October 1998 until May 1999 using the Line Transect Method (LTM). The distribution and population densities of the Great Argus was conducted by line transect survey. The position of calling males was mapped.